Rape, Intoxication and the Concept of Consent - Sveinsdóttir, Þorbjörg (Nordisk Tidsskrift for Kriminalvidenskab, 2020)
Abstract In this article the applicability of the concept of consent is examined in rape cases where the complainant is voluntarily intoxicated. Consent has been at the core of the offence of rape in England for quite some time and the applicability of the concept in such cases in England is examined. The article argues that the concept of consent has not been adequately able to address cases of voluntary intoxication in England, demonstrating that the concept of consent is particularly problematic when it comes to such cases, both due to its ambiguous meaning and its subjective nature. It is furthermore argued that a coercion-based definition of rape, which the Nordic countries have all until recently adhered to, may provide for a more workable yardstick in cases of voluntary intoxication. The recent introduction of a consent-based definition of rape in Swedish and Icelandic law is examined along with how it applies to cases of voluntary intoxication. The article concludes that although both Sweden and Iceland have recently amended their rape laws as to include consent-based definitions of rape, both countries have in effect adhered to a coercion-based model when it comes to cases of voluntary intoxication, relying on yardsticks focusing on the physical.